Assessment of the Quality of Industrial Wastewater in Three Metropolitan Cities in Bangladesh - Sultana, N; Muktadir, H; Chowdhury, MAH; Baten, MA (Journal of Environmental Science and Natural Resources, 2017)
This study was conducted to assess the quality of different industrial wastewater. Some physicochemical parameters viz., pH, EC, TDS, Na+, K+, Ca++, Mg++, CO32-, HCO3-, Cl-, SO42-, PO43- including heavy metal contents like Pb, Cd, Ni, Cr, As, Zn and Cu concentration from collected wastewater samples were analyzed. Atomic Absorption Spectrophotometer was used for analyzing the heavy metals in the wastewater samples. The results revealed that, the values of pH, EC, TDS ranged between 6.44-9.0, 471-4307 ?S cm-1, 1952-5209 mg L-1, respectively. The higher mean concentrations of Na+, K+, Ca++, Mg++, CO3-, HCO3-, Cl-, SO42-, PO43- were 1407.8, 27.9, 69.9, 76.6, 2.7, 11.7, 1688, 76.6, 6.1 mg L-1, respectively. The mean concentration of Cd, Ni, Cr, Zn, and Cu was 0.17, 0.87, 85.73, 0.80, and 1.56 mg L-1, respectively. Among trace elements Ni and Cd, Zn and Cd, Zn and Cr showed a positive relationship. To avoid the harmful effects of wastewater on environment it is imperative to treat industrial effluents before discharge into open environment. J. Environ. Sci. & Natural Resources, 9(2): 21-25 2016